Toponyms in Banyumas as Representation of Banyumas Community Culture - Resticka, Gita Anggria; Nurdiyanto, Erwita; Marahayu, Nila Mega (Faculty of Humanities, Universitas Jenderal Soedirman, 2023)
Naming is searching for language symbols to describe objects, concepts, and processes by utilizing vocabulary through changes in meaning or the creation of words. Toponyms are used as the identity of a place because they come from the results of the culture of the people in the area, which originate from the reciprocal relationship with the environment, in this case, namely language. The name of the place cannot be separated from the characteristics or things related to the place, such as the name of the sub-district in Banyumas Regency. This research is descriptive qualitative. The object of study of toponyms in this research is the naming of sub-districts in Banyumas Regency, which have physical and cultural characteristics that can be traced from an event or event in the past. The toponymy of sub-districts in Banyumas Regency can be a source of local history for the Banyumas people. Myths are passed down from generation to generation as part of the local history of place names. The history of naming is an oral tradition passed down from generation to generation, so naming places has cultural value. There are also local wisdom values in the sub-district toponymy in Banyumas Regency. The research results show that the sub-district toponyms in Banyumas Regency can trace the values behind the naming stories, namely the social and cultural values of the stories or myths of the Banyumas people. This local topography value in Banyumas Regency can be used as a source of learning for the younger generation.